2023
DOI: 10.1177/10778012231153361
|View full text |Cite
|
Sign up to set email alerts
|

Different Scripts, Different Casts: A Crime Script Analysis Indicating Intimate Partner Violence Is Not All the Same

Abstract: Crime script analysis was used to analyze intimate partner violence diversity by identifying variables significantly associated with different script tracks. Qualitative thematic analysis using official police administrative data from Queensland, Australia, was used to develop an intimate partner violence protoscript ( n = 40), followed by quantitative hierarchical cluster analysis and cross-tabulations to examine diversity within scripts. Four diverse script tracks were identified: “escalating jealousy,” “per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Recent research (Carney et al , 2023; Dehghanniri and Borrion, 2021) has demonstrated that while qualitative approaches allow for the intricacies of an incident to be examined, quantitative methods benefit from a more transparent reporting of findings. As such, while our analysis was qualitative, we supported our findings (presented in Tables 1–5: Source: Created by authors) with frequency scores to better support the reproducibility of findings in different samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research (Carney et al , 2023; Dehghanniri and Borrion, 2021) has demonstrated that while qualitative approaches allow for the intricacies of an incident to be examined, quantitative methods benefit from a more transparent reporting of findings. As such, while our analysis was qualitative, we supported our findings (presented in Tables 1–5: Source: Created by authors) with frequency scores to better support the reproducibility of findings in different samples.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a pathways approach has been applied to explore how life events and other factors that may influence an individual’s trajectory towards becoming a criminal or a terrorist (Carney et al , 2023; Jensen et al , 2020a; Knight and Keatley, 2020; Keatley et al , 2021). Pathways refer to the sequential temporal route that is shaped, guided and directed by the influences that the individual encounters.…”
Section: Introductionmentioning
confidence: 99%